PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK PERANGKINGAN KINERJA PEGAWAI TERBAIK DI STIKES GETSEMPENA LHOKSUKON - Mukhroji Mukhroji; Fadhlina Fadhlina (JURNAL ILMIAH INFORMATIKA, 2021)
Employee performance appraisal in an institution is an absolute thing that needs to be done, where employees compete fiercely to get the best category in order to achieve a brilliant career in that agency. Every agency needs qualified, honest, educated, and disciplined employees to ensure good quality. Each agency has a different and selective way of determining good employees, this can also be a consideration for agency leaders to choose the best employee criteria so that they are worthy of being placed in strategic positions. From some of the descriptions above, this research needs to be carried out which aims to assist a leader in an institution in determining the best employees. This study applies the Simple Additive Weighting (SAW) method for decision making to rank the best employee performance. The steps taken are determining the criteria and attributes that will be the reference in the decision matrix assessment so that the final result obtained is the ranking of the best criteria and attribute values ​​that can help the leadership of an agency to make informed decisions in determining the best employees to be placed in strategic positions in these agencies.